Social and psychological profile of the modern Russian consumer: Values and preferences - Kuljamina O., Babakaev S., Vinogradova M., (Opción, 2019)
The goal of this work is to identify the axiological type of Russian consumer, as well as to reveal certain gaps in presentation and understanding of the social and psychological profile of Russian consumers via sociological and marketing approaches. As a result, goods are perceived as tools that help a person to achieve goals associated with a certain system of values. It is concluded that while compiling Russian consumer’s social and psychological profile, it is important to consider the leading role of institutional stereotypes and archetypes of individual and mass consciousness that define the consumer values and preferences.